Dormitory-Based Intensive Religious Education in Jakarta - Meliyana, Reza Rosa; Lismawati, Lismawati; Arifuddin, Farchan (CV. Rayyan Dwi Bharata, 2024)
Dormitory-based intensive religious education is an alternative educational approach applied in religious schools or Islamic boarding schools. This research aims to describe intensive dormitory-based religious education in Jakarta with a case study at the Al Hamid Cilangkap Islamic Boarding School. This research uses a descriptive qualitative approach. Data collection was carried out through observation, interviews and document study. The results of the research show that intensive religious education at the Al Hamid Islamic Boarding School introduces an integrated education system between Islamic boarding schools and formal schools, requiring students to live in dormitories. There are two types of learning, namely in formal schools and additional learning in dormitories which focuses on deepening religious material. Apart from that, positive habits and self-development of students are also implemented. This intensive religious education has succeeded in forming the character of the students, motivating them to learn, and producing many achievements both academic and non-academic. In conclusion, dormitory-based intensive religious education is effective in building character, increasing learning motivation, and developing the potential of students.